An Investigation on Awareness and Users’ Perception on Effective Utilization of OPAC in the University Libraries of Haryana - Mithu Dey (International Journal of Advanced Science and Technology, 2020)
This paper explores to investigate an awareness and user perception on the effectiveness of OPAC at the university libraries of Haryana. The present study based on descriptive survey research design. The investigation used primary data and closed questionnaire method for data collection.1000 samples of the questionnaire were distributed randomly among the students, research scholars and teaching faculty of university libraries of Haryana. Out of which 840 (84%) complete questionnaire were collected questionnaire were collected for analysis. 719 (71.9%) questionnaires were considered to conduct further study on OPAC usage in these four university libraries. The paper highlights various aspects of usage of OPAC such as frequency of use, awareness on OPAC, users’ perception, purpose of using OPAC, different searching techniques used, problems faced while using OPAC, need of satisfaction level etc. This paper highlights emphasizes on need of training / library orientation programme on OPAC to improve knowledge and skills of users. The findings of the study This study depicts that 80.4% uses were aware of OPAC out of which 71.9% users refers OPAC for searching various information in the respective libraries to fulfill their reading purpose. The study was an attempt to provide meaningful realistic evidence for librarians to put best possible effort to increase the usage of OPAC in university libraries of Haryana.